Incorporating Cutaneous and Wound Bacterial Bioburden Biomarkers into Clinical Research: A Review of Best Practices. (September 2016) - Honaker, Jeremy; Ammons, Christie; Kelechi, Teresa
Abstract : PURPOSE: To provide information about initiating interdisciplinary research related to microbiomes and their role in human immunity, disease, and metabolic processes. TARGET AUDIENCE: This continuing education activity is intended for physicians and nurses with an interest in skin and wound care. OBJECTIVES: After participating in this educational activity, the participant should be better able to: 1. Describe techniques to identify and characterize bacterial bioburden. 2. Identify optimal collection, transport, and storage of samples. ABSTRACT: OBJECTIVE: The purpose of this review is to provide a roadmap for clinical scientists interested in integrating bacterial bioburden (BB) biomarkers into the next generation of cutaneous or wound disease research studies. DISCUSSION: Complex relationships exist between humans and their microbiome. Until now, clinical scientists have been limited in fully characterizing relationships between humans and their microbiome. Recent technological innovations, such as next-generation DNA sequencing, also known as deep sequencing or pyrosequencing, have enhanced clinicians' capacity to identify, characterize, and elucidate the role of BB (ie, bacterial load, diversity, pathogenicity) in human immunity, disease, and metabolic processes. The understanding of common terminology, intervening variables that influence BB, limitations of next-generation DNA sequencing, and specimen selection, collection, transport, and storage practices are needed to support interdisciplinary communication, research design, and integrity of the specimen. CONCLUSION: This review serves as a primer for building foundational knowledge in microbiome research, which will aid clinical scientists with initiating interdisciplinary communication necessary for scientific team building.